Application of a multi-component cyclocondensation to develop a bioactive molecular scaffold - Chatterjee, Sankar (European Journal of Chemistry, 2016)
A molecular scaffold containing a furanoquinoline motif that offered a unique molecular architecture for 5-hydroxytryptamine 6 receptor antagonism was generated by a multi-component cyclization reaction.